2012
DOI: 10.5812/jjm.4129
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Vancomycin and Cefazolin Therapeutic Effect with Povidone Iodine on Corneal Ulcer in Rabbits

Abstract: Lower effect of povidone iodine may be the result of the lack of deep penetration of this drug into the corneal stroma, but other factors may be involved. Background: Corneal ulcer is a common cause of blindness in developing countries, as itleads to corneal perforation and blindness if not properly treated. Objectives: This study aimed to determine the effects of intraocular 5 % and 10 % topical povidone iodine in the treatment of bacterial corneal ulcer in a rabbit model, comparing the effectiveness of vanco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The effect of povidone-iodine as a broad spectrum antiseptic to reduce the incidence of endophthalmitis in the preoperative preparation period, has been reported by many studies ( 5 - 8 , 10 - 12 , 14 , 16 , 17 ), which showed the use of povidone-iodine 5% in the fornix before the surgery, significantly decreases conjunctival colonies. Feghhi and colleagues approved the efficacy of povidone-iodine on corneal ulcers compared with standard antibiotics in animals ( 22 ). Thus, the most acceptable method for preparation of the eyelid and conjunctiva, is the use of povidone-iodine, however the preferred method for the end of the surgery still depends on the surgeon’s opinion ( 14 - 16 , 18 - 20 , 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of povidone-iodine as a broad spectrum antiseptic to reduce the incidence of endophthalmitis in the preoperative preparation period, has been reported by many studies ( 5 - 8 , 10 - 12 , 14 , 16 , 17 ), which showed the use of povidone-iodine 5% in the fornix before the surgery, significantly decreases conjunctival colonies. Feghhi and colleagues approved the efficacy of povidone-iodine on corneal ulcers compared with standard antibiotics in animals ( 22 ). Thus, the most acceptable method for preparation of the eyelid and conjunctiva, is the use of povidone-iodine, however the preferred method for the end of the surgery still depends on the surgeon’s opinion ( 14 - 16 , 18 - 20 , 23 ).…”
Section: Discussionmentioning
confidence: 99%